Health status has improved more in women than in men with rheumatoid arthritis from 1994 to 2009: results from the Oslo rheumatoid arthritis register. Issue 1 (15th October 2013) - Austad, C; Kvien, T K; Olsen, I C; Uhlig, T
Abstract : Objective: To examine changes in patient reported outcome measures (PROs) over 15 years in a representative population of patients with rheumatoid arthritis (RA), with a particular focus on gender differences. Patients and methods: Patients in the Oslo RA register filled in questionnaires including the Modified Health Assessment Questionnaire (MHAQ), the Short-Form 36 (SF-36) with physical (PCS) and mental component summaries and derived utility (SF-6D), visual analogue scales (VAS) for pain, patient global assessment of disease (PtGA) and fatigue, and checklists of medication commonly used in the treatment of RA. Data were collected at five time points during a 15-year period from 1994. Mixed model analyses were used to analyse longitudinal changes in PROs from 1994 to 1996, 2001, 2004 and 2009. Results: Data were available from 829–1025 RA patients at each time point. PROs were statistically significantly improved from 1994 to 2009 (MHAQ, SF-36 PCS, SF-6D, pain VAS, PtGA VAS and fatigue VAS; all p<0.001), and also with clinically important improvement. Men reported significantly better health status than women in 1994, but women improved significantly more than men over 15 years with a reduction of the gender gap in 2009. Antirheumatic medication was increasingly used over 15 years with no gender differences. Conclusions: RA patients reported statistically significantly improved health status for most PROs from 1994 to 2009. Women improved most, and although they still reported higher disease impact than men, the gender differences were small at the final data collection in 2009.